2018
DOI: 10.1111/1756-185x.13272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induction therapy on circulating T‐helper 17 and T‐regulatory cells in active proliferative lupus nephritis

Abstract: Circulating Th17 cells were significantly raised in patients with active proliferative LN and showed a significant reduction in responder patients following therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Our results are in accordance with previous studies which demonstrated up-regulation of the Th17-axis in SLE compared to control, but failed to find an association between Th17 responses and disease activity [9][10][11]. Moreover, in the available literature there was usually no association between increased levels of IL-17A or a higher fraction of Th17 cells and the presence of nephritis in SLE patients [8][9][10][11]14] with only few studies demonstrating clear expansion of Th17 in more severe proliferative LN [26,27]. Inconsistencies between various studies may be attributed to different strategies in detection of the Th17 subset, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance with previous studies which demonstrated up-regulation of the Th17-axis in SLE compared to control, but failed to find an association between Th17 responses and disease activity [9][10][11]. Moreover, in the available literature there was usually no association between increased levels of IL-17A or a higher fraction of Th17 cells and the presence of nephritis in SLE patients [8][9][10][11]14] with only few studies demonstrating clear expansion of Th17 in more severe proliferative LN [26,27]. Inconsistencies between various studies may be attributed to different strategies in detection of the Th17 subset, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…2A, 2B), these effects were inhibited in the Tris DBA + ASLN mice. In contrast, Treg cells have been shown to play a protective role in SLE (31,38) and LN (39,40). We determined the population of Foxp3 + CD25 + CD4 + Treg cells, and the results showed that a significantly increased percentage of Foxp3 + CD25 + CD4 + Treg cells was observed at week 5 in the Tris DBA + ASLN mice compared with the Vehicle + ASLN mice (Fig.…”
Section: Tris Dba Modulated T Cell Function In Asln Micementioning
confidence: 91%
“…1 Furthermore, circulating Th17 cells were significantly raised in patients with active proliferative lupus nephritis, but significantly reduced in responder patients following therapy. 2 The role of Th17 cells in the pathogenesis of SLE provides a potential and promising approach for treatment of SLE.…”
Section: Introductionmentioning
confidence: 99%